2020
DOI: 10.1186/s12913-020-06001-y
|View full text |Cite
|
Sign up to set email alerts
|

Persistent symptoms after Covid-19: qualitative study of 114 “long Covid” patients and draft quality principles for services

Abstract: Background Approximately 10% of patients with Covid-19 experience symptoms beyond 3–4 weeks. Patients call this “long Covid”. We sought to document such patients’ lived experience, including accessing and receiving healthcare and ideas for improving services. Methods We held 55 individual interviews and 8 focus groups (n = 59) with people recruited from UK-based long Covid patient support groups, social media and snowballing. We restricted some foc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
570
5
27

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(651 citation statements)
references
References 41 publications
49
570
5
27
Order By: Relevance
“…This finding is in line with earlier study among African Ebola survivors who identified patients caring for each other as a source of resilience for self-preservation, highlighting the prevalence of humanity and strength in crisis across different cultures and communities. 14 Our findings further support Ladds and colleagues’ 12 call to establish online peer support groups during and after COVID-19 to share patients’ experiences and knowledge about the illness.…”
Section: Discussionsupporting
confidence: 77%
“…This finding is in line with earlier study among African Ebola survivors who identified patients caring for each other as a source of resilience for self-preservation, highlighting the prevalence of humanity and strength in crisis across different cultures and communities. 14 Our findings further support Ladds and colleagues’ 12 call to establish online peer support groups during and after COVID-19 to share patients’ experiences and knowledge about the illness.…”
Section: Discussionsupporting
confidence: 77%
“…41 To date, inconsistent diagnoses of long COVID have made it difficult to ascertain the demographic profile of people with long COVID at a population level, with women disproportionately represented in symptom studies 42 and qualitative research 10 11 along with people of higher educational background. 10 We took steps to achieve a diverse sample in terms of age, gender and ethnicity, but did not collect information on socioeconomic status or geographical characteristics of participants, so are unable to draw firm conclusions about how these factors may influence our findings. Nevertheless, our participants were recruited from a research interest database indicating a level of engagement and access to online research, and our sample might not be representative of the long COVID population as a whole.…”
Section: Limitationsmentioning
confidence: 99%
“…Evidence describing the condition is scarce, but is starting to emerge on the long-term health impairment and organ damage following COVID-19 [7][8][9][10][11] . Patients are struggling to access adequate recognition, support, medical assessment and treatment for their condition, particularly those with no lab evidence of their infection during the first wave of the pandemic when testing was not accessible to those not hospitalised in the initial phase of their COVID-19 disease 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…This may result in variation in diagnosis and referral among different clinicians, leading to inequalities in recognition and accessing services 23 . Many of those infected in spring 2020 did not have access to testing and therefore have struggled to receive recognition, diagnosis and support 12,13 . This study was conceived following conversations with people with Long Covid in the community who perceived a lack on data of COVID-19 sequelae in non-hospitalised individuals and felt a need for their experience to be explored and documented.…”
Section: Introductionmentioning
confidence: 99%